Survei status gizi balita di Agats, Asmat, Papua: Analisis situasi pascakejadian luar biasa gizi buruk - Maria Fransiska Pudjohartono; Hanggoro Tri Rinonce; Josephine Debora; Pritania Astari; Monica Gisela Winata; Fadli Kasim (Journal of Community Empowerment for Health, 2019)
A recent extraordinary event of malnutrition in children in Asmat, Papua, Indonesia has drawn enormous attention. To help in post-emergency rehabilitation, Gadjah Mada University sent a Kuliah Kerja Nyata – Peduli Bencana (KKN-PB) team to Agats, Asmat in March 17 – April 20, 2018. As part of situation analysis, the team surveyed the nutritional status of under five-years-old children in Agats, Asmat. The subjects were under five-year-old children coming to posyandus in five areas in Agats in March-April 2018. The data of sex, age, weight, and height were obtained, then the nutritional status in the form of Z-scores for weight-for-age (WAZ), height-for-age (HAZ), and weight-for-height (WHZ) was calculated using WHO Anthro version 3.2.2 software. Nutritional status was determined based on criteria from World Health Organization (WHO). Among the 372 children, 35 (9.4%) children were underweight and 7 (1.9%) were severely underweight. Twenty one (5.7%) children were stunted and 12 (3.2%) were severely stunted. As many as 23 (6.2%) children were found to be wasted and 6 (1.6%) were severely wasted. The percentages of children with malnutrition found in this survey were lower than the percentages for Indonesia and Papua overall, but percentages in two posyandus were higher than the national and Papua percentages. The relatively low total percentages may be accounted for by concentration of malnutrition cases in districts other than Agats and lack of coverage of children absent from posyandu. Prevalence of malnutrition varied in different age groups possibly due to inadequacy of complementary foods, changes in incidence of infections, and addition of siblings. Further surveys are needed using home visits that will also enable to analyze of socio-economic factors at the same time as nutritional status determinants in Agats and other districts in Asmat.